Water Shortage Problems and Their Elimination on Measures - Yadgarova Shahodat (Scholars Digest Publishing, 2023)
In the countries of Central Asia, including the Republic of Uzbekistan, the use of water resources, the economical use of this precious resource is one of the urgent problems of today. Correct use of clean drinking water, preventing water wastage in agriculture in the region is the only way to solve the above issues. This article covers the water shortage, the experiences of foreign countries on saving them, and the suggestions for introducing these experiences.
Keywords: rivers, water resources, water towers, global warming, melting glaciers, rational use of water, hydrometeorological situation analysis, artificial intelligence water treatment.